Our Affairs from England - Vince, Máté (Hungarian Journal of English and American Studies, 2020)
Book review: Kiséry, András. Hamlet’s Moment. Drama and Political Knowledge in Early Modern England. New York, Oxford: Oxford UP, 2016. 340 pages. ISBN 9780198746201. Hb. £66.